Improving Students’ Skill In Writing Through Cooperative Learning Strategy At Bilingual Class Of Essenville School Bandung: - - Batubara, Lili Suryani (LPPAIK Universitas Muhammadiyah Bandung, 2025)
Kata Kunci:Writing Skill; Cooperative Learning; Bilingual student There are so many problems faced by the teachers in teaching English as foreign language. The most difficult problem is teaching and learning writing. In learning writing especially writing recount text, students have many difficulties in analysing the grammatical features of a text. In relation to the improving the students’ writing, the cooperative concept is occurred in teaching recount text. One strategy in cooperative learning is think pair share. In this case, the researcher is eager to investigate and examine the possibility of improvement in students’ skill in writing recount through cooperative learning by using think pair share. And finally to find out weather this technique of cooperative learning can give more improvement to the students in writing recount. The study used descriptive qualitative research which focused on the natural characteristic of data by using classroom action research. The findings showed that, there was an increase of students’ skill in writing recount from cycle 1 to cycle 2. Then, face to face interaction as one of element of cooperative learning contributed very much in improving students’ writing skill for for Bilingual class, grade VII, Essenville Junior High School (Sekolah Menengah Pertama:SMP).